The material situation of factory workers in the Vitebsk province in 1907–1914 - Maslouski, Evgeny V. (Journal of the Belarusian State University. History, 2018)
On the basis of archival and statistical sources the analysis of the earnings and expenses of the average worker in Vitebsk province in 1907–1914 is given, where the level of wages was lower than in other Belarusian provinces. The dynamics of changes in the average wage of workers and prices for socially important products and services is compared. The financial condition of the worker’s family is determined. For the first time in national historiography attention to the participation of charitable societies in the workers’ budget formation, which allowed to offset part of the costs, is drawn.
Keywords: budget; Belarus; salary; charity; worker; social status; prices; industry; 1907–1914; proletariat; factory; Vitebsk province